(untitled) (Research, Society and Development, 2022)
This article presents the results of an exploratory research, of the case study type, and aimed to understand how relationships between students with High Abilities/Giftedness are built, from the participants’ point of view. The context in which the research was developed was a Resource Room of a municipal public school in Porto Alegre (RS), which offers Specialized Educational Assistance (AH/SD) to students with Abilities/Giftedness (AH/SD). The instruments used were direct observation and a questionnaire applied to six students, aged between 10 and 15 years. The analysis of the study data allowed us to identify certain perceptions, behaviors and feelings that are associated with the coexistence of these adolescents in the AEE. The following stood out: mutual support, partnership, raising self-esteem, common interests, acceptance of their characteristics. It was concluded that this service is very important for those students because, according to them, from these interactions they got to know each other better and feel more secure and confident.